Hair penalties: the negative influence of Afrocentric hair on ratings of Black women’s dominance and professionalism - Opie, Tina R.; Phillips, Katherine W. (Frontiers in Psychology, 2015)
Purpose: Women are penalized if they do not behave in a stereotype-congruent manner (Heilman, 1983, 2001; Eagly and Carli, 2007). For example, because women are not expected to be agentic they incur an “agency penalty” for expressing anger, dominance or assertiveness (Rudman, 1998; Rudman and Glick, 1999, 2001; Eagly and Karau, 2002; Rudman and Fairchild, 2004; Brescoll and Uhlmann, 2008; Livingston et al., 2012). Yet, all women are not equally penalized (Livingston et al., 2012). We make a novel contribution by examining how both White and Black evaluators respond to displays of Black women’s dominance, in this case, whether Black women choose to wear Afrocentric or Eurocentric hairstyles. Design/methodology/approach: We conducted three experimental studies to examine the influence of target hairstyle and participant race on ratings of the target’s professionalism (Studies 1, 2, and 3) and dominance (Study 2). Study 1 was an online experimental study with 200 participants (112 females, 87 males, 1 missing gender; 160 Whites, 19 Blacks, 11 Latinos, 7 Asian Americans and 3 who identify as “other”; Mage = 35.5, SD = 11.4). Study 2 was an online experimental study with 510 participants (276 women, 234 males; 256 Blacks, 254 Whites; Mage = 41.25 years, SD = 12.21). Study 3 was an online experimental study with 291 participants (141 Blacks, 150 Whites, Mage = 47.5 years, SD = 11.66). Findings: Black, as compared to White, evaluators gave higher agency penalties to Black employment candidates when they donned Afrocentric versus Eurocentric hair, rating them as more dominant and less professional. Implications: The present research illustrates the significance of considering both target and evaluator race when examining the influence of agency, and specifically dominance, on ratings of professionalism.